Contemporary Politics in Latin America: Anti-Political Bolsonaro’s Speech - ILIKOVA, L.E.; KOCHKIN, Á.A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article analyses the contemporary political processes in Brazil, especially the process of reframing the expression “to play politics". Authors examine the subjects involved in this process of political changes, the relationship between politics, democracy, and the concept of a democratic State of law. As the president, Bolsonaro is a considerable actor in politics in all Latin America, not only in Brazil, a special attention is made to his activity and public political discourse.RESUMEN Este artículo analiza los procesos políticos contemporáneos en Brasil, especialmente el proceso de reformular la expresión "jugar a la política". Los autores examinan los temas involucrados en este proceso de cambios políticos, la relación entre política, democracia y el concepto de un Estado de derecho democrático. Como el presidente Bolsonaro es un actor considerable de política en toda América Latina, no solo Brasil, se presta especial atención a su actividad y discurso político público.